The Use of Instagram in the Sports Biomechanics Classroom - Navandar, Archit; Frías López, Daniel; Alejo, Lidia B. (Frontiers in Psychology, 2021)
Students in higher education habitually use mobile devices such as smartphones and tablets, specifically using social networks on them for staying updated on current affairs, communication between one another, and entertainment. However, its use as a potential medium for active learning especially in times of distance learning has not been studied in depth. Instagram is the fastest growing social network in the world and its graphical interface makes it a useful learning tool for a theoretical-practical subject such as biomechanics, where movement is analyzed. The main objective was to evaluate the change in perception of students in the use of Instagram as a learning medium for qualitative biomechanical analysis as a part of their undergraduate sports science program. 171 students filled out a questionnaire on the use of smartphones, social networks, and specifically Instagram before and after doing an assignment of qualitative analysis that was carried. The results indicated a positive change in the perspective of the students when asked if class assignments can be done on mobile devices (p=0.002) and social media (p<0.001). The students also indicated a greater interest in doing assignments via social networks (p<0.001), especially in the subject of biomechanics (p<0.001). They also cited that Instagram is a useful source for information on sports biomechanics (p=0.015) and could be used to make observations of sporting movements (p=0.043). The results indicated that an introduction of familiar devices in undergraduate teaching could produce a positive change in perception of using such methodologies and facilitating learning. The students, who use smartphones very frequently in their daily lives, and specifically, many use it for browsing social networks, find the platform to be very useful in finding and sharing information related to sports and specifically in sports biomechanics. The visual aspect of social networks like Instagram can help engage them with active learning strategies in a subject like biomechanics.